Modulation of cerebellar cortical, cerebellar nuclear and vestibular nuclear activity using alternating electric currents - Avlar, Billur; Rahman, Ramia; Vendidandi, Sai; Cetinkaya, Esma; Asan, Ahmet S.; Sahin, Mesut; Lang, Eric J. (Frontiers in Systems Neuroscience, 2023)
Introduction. Cerebellar transcranial alternating current stimulation (ctACS) has shown promise as a therapeutic modality for treating a variety of neurological disorders, and for affecting normal learning processes. Yet, little is known about how electric fields induced by applied currents affect cerebellar activity in the mammalian cerebellum under in vivo conditions. Methods. Alternating current (AC) stimulation with frequencies from 0.5 - 20 Hz were applied to the surface of the cerebellum affected cerebellar activity in anesthetized rats. Extracellular recordings were obtained from Purkinje cells, cerebellar and vestibular nuclear neurons, and other cerebellar cortical neurons. Results and Discussion. AC stimulation modulated the activity of all classes of neurons. Cerebellar and vestibular nuclear neurons most often showed increased spike activity during the negative phase of the AC stimulation. Purkinje cell simple spike activity was also increased during the negative phase at most locations, except for the cortex directly below the stimulus electrode, where activity was most often increased during the positive phase of the AC cycle. Other cortical neurons showed a more mixed, generally weaker pattern of modulation. The patterns of Purkinje cell responses suggest that AC stimulation induces a complex electrical field with changes in amplitude and orientation between local regions that may reflect the folding of the cerebellar cortex. Direct measurements of the induced electric field show that it deviates significantly from the theoretically predicted radial field for an isotropic, homogeneous medium, in both its orientation and magnitude. These results have relevance for models of the electric field induced in the cerebellum by AC stimulation.